Evidence of False Positivity for Vibrio Species Tested by Gastrointestinal Multiplex PCR Panels, Minnesota, 2016–2018. (16th May 2021) - Decuir, Marijke; Fowler, Randal C; Cebelinski, Elizabeth; Smith, Kirk; Boxrud, David; Medus, Carlota
Abstract: Background: Syndromic gastrointestinal multiplex polymerase chain reaction (PCR) panels (GMPPs) are used by an increasing number of clinical laboratories to identify enteric pathogens. Vibrio species are included on GMPPs, but because of the low prevalence of vibriosis, performance characteristics for these panels have been difficult to measure. Methods: All Vibrio spp. cases identified by GMPPs in Minnesota during 2016–2018 (n = 100) were assessed to identify differences between culture-confirmed cases and those that were PCR-positive only. Results: Overall, 47% of cases had Vibrio species recovered by culture. Two GMPPs were used in Minnesota, Verigene EPT and FilmArray GIP, and the recovery rate of Vibrio spp. was significantly different between these platforms (Verigene EPT 63%, compared with FilmArray GIP 28%). No distinct seasonality was identified among GMPP-positive, culture-negative cases, whereas culture-confirmed case incidence peaked during July and August. Among cases with no other pathogen detected by the GMPP, confirmed cases reported a lower rate of bloody diarrhea (odds ratio [OR], 0.7; P  = .004) and were less likely to have a symptom duration >14 days (OR, 0.3; P  = .04). Confirmed cases were also more likely to include reports of consuming food items typically associated with Vibrio spp. infection or to have another likely source of infection (eg, international travel or contact with an untreated body of fresh or salt water or marine life; OR, 9.6; P  = .001). Conclusions: The combined findings indicate that cases identified by GMPP that did not have culture confirmation were less likely to include symptoms or exposures consistent with vibriosis. These findings emphasize the need for improvements to testing platform specificity and the importance of combining clinical and exposure information when diagnosing an infection. This study underscores the importance of maintaining the ability to culture Vibrio species to aid in accurate diagnoses.